Chromosome-level genome assembly of Przevalski’s partridge (Alectoris magna) - Xumin Wang; Wenhao Xia; Xindong Teng; Wanying Lin; Zhikai Xing; Shuang Wang; Xiumei Liu; Jiangyong Qu; Wei Zhao; Lijun Wang (Scientific Data, 2023)
Abstract Przevalski’s partridge (Alectoris magna) is one of the birds in the genus Alectoris endemic to China. The distribution of A. magna was narrow, and it was only found in parts of the Qinghai, Gansu, and Ningxia provinces. A. magna was considered a monotypic species until it was distinguished into two subspecies. However, external morphological characteristics, rather than genetic differences or evolutionary relationships, are now commonly used as evidence of subspecies differentiation. In this study, a chromosome-level reference genome of A. magna has been constructed by combining Illumina, PacBio and Hi-C sequencing data. The 1135.01 Mb A. magna genome was ultimately assembled. The genome showed 96.9% completeness (BUSCO), with a contig N50 length of 23.34 Mb. The contigs were clustered and oriented on 20 chromosomes, covering approximately 99.96% of the genome assembly. Additionally, altogether 19,103 protein-coding genes were predicted, of which 95.10% were functionally annotated. This high-quality genome assembly could serve as a valuable genomic resource for future research on the functional genomics, genetic protection, and interspecific hybridization of A. magna.